Type I Interferon Receptor Signaling of Neurons and Astrocytes Regulates Microglia Activation during Viral Encephalitis - Chhatbar, Chintan; Detje, Claudia N.; Grabski, Elena; Borst, Katharina; Spanier, Julia; Ghita, Luca; Elliott, David A.; Jordão, Marta Joana Costa; Mueller, Nora; Sutton, James; Prajeeth, Chittappen K.; Gudi, Viktoria; et al. (Cell reports (Cambridge), 2018)
In sterile neuroinflammation, a pathological role is proposed for microglia, whereas in viral encephalitis, their function is not entirely clear. Many viruses exploit the odorant system and enter the CNS via the olfactory bulb (OB). Upon intranasal vesicular stomatitis virus instillation, we show an accumulation of activated microglia and monocytes in the OB. Depletion of microglia during encephalitis results in enhanced virus spread and increased lethality. Activation, proliferation, and accumulation of microglia are regulated by type I IFN receptor signaling of neurons and astrocytes, but not of microglia. Morphological analysis of myeloid cells shows that type I IFN receptor signaling of neurons has a stronger impact on the activation of myeloid cells than of astrocytes. Thus, in the infected CNS, the cross talk among neurons, astrocytes, and microglia is critical for full microglia activation and protection from lethal encephalitis. [Display omitted] •VSV infection via the olfactory route leads to accumulation of microglia in the OB•Following infection, microglia form an innate immune barrier in the OB•The microglia barrier prevents viral CNS penetration via the olfactory route•IFNAR signaling of neurons and astrocytes regulates microglia barrier formation The mechanisms restricting viral entry into the CNS via the olfactory route were unclear. Chhatbar et al. show that intercellular communication within the olfactory bulb (OB) among neurons, astrocytes, and microglia orchestrates formation of a microglial barrier that restricts the spread of the virus into the CNS.